PENGUATAN LITERASI DIGITAL GURU MELALUI PENERAPAN EDUNAV: STUDI KASUS SEKOLAH KHARISMA BANGSA - Faiza, Fikis Silmi; Ratnaningsih, Siti; Hakiem, Nashrul (STKIP Pesisir Selatan, 2025)
This study aims to analyze the implementation of Edunav in improving teachers' digital literacy and its impact on learning transformation at Sekolah Kharisma Bangsa. Using a descriptive qualitative approach and content analysis techniques, this study explores the Edunav adoption process starting from socialization, training, use of core features, to its integration in management and learning practices. The findings of the study show that Edunav is able to strengthen the four dimensions of teachers' digital literacy technical, pedagogical, informational, and ethical which further encourages improvement in the quality of learning planning, evaluation, and data-based decision-making through learning analytics. The implementation of Edunav is also influenced by various supporting factors, such as infrastructure readiness, management support, collaborative culture, and ongoing training programs. However, a number of challenges remain, such as digital literacy gaps between teachers, technical barriers, and resistance to pedagogical changes. Theoretical analysis based on multidimensional digital literacy and the TPACK framework show that the effectiveness of Edunav is highly dependent on teachers' ability to integrate technology with pedagogical strategies and learning content. This research emphasizes the importance of targeted professional development, consistent digital policies, and enhancement of LMS features to support the digital transformation of education in a sustainable manner.